2021
DOI: 10.3897/mycokeys.82.68299
|View full text |Cite
|
Sign up to set email alerts
|

Two new brown rot polypores from tropical China

Abstract: Brown-rot fungi are types of fungi that selectively degrade cellulose and hemicellulose from wood and are perhaps the most important agents involved in the degradation of wood products and dead wood in forest ecosystem. Two new brown-rot species, collected from southern China, are nested within the clades of Fomitopsis sensu stricto and Oligoporus sensu stricto, respectively. Their positions are strongly supported in the Maximum Likelihood phylogenetic tree of the concatenated the internal transcribed spacer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Cui & Shun Liu formed separate lineages, respectively ( Figure 1 ). In addition, the current phylogenetic analyses also showed that Fomitopsis and other related brown-rot fungal genera clustered together within the antrodia clade, which are consistent with previous studies ( Ortiz-Santana et al, 2013 ; Han et al, 2016 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Cui & Shun Liu formed separate lineages, respectively ( Figure 1 ). In addition, the current phylogenetic analyses also showed that Fomitopsis and other related brown-rot fungal genera clustered together within the antrodia clade, which are consistent with previous studies ( Ortiz-Santana et al, 2013 ; Han et al, 2016 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Cui, Hai J. Li & M.L. Han also distribute in Hainan Province of China, but F. bambusae differs by having bluish-gray to pale mouse-gray pore surface when fresh, becoming mouse-gray to dark gray when dry, smaller pores (6–9 per mm), smaller and cylindrical to oblong ellipsoid basidiospores (4.2–6.1 × 2–2.3 μm), and grows on bamboo ( Zhou et al, 2021 ); F. cana differs by having cream to straw colored pore surface when young which becoming mouse-gray to dark gray with age, a trimitic hyphal system, smaller and cylindrical to oblong-ellipsoid basidiospores (5–6.2 × 2.1–3 μm; Li et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The internal transcribed spacers (ITS), large subunit of nuclear ribosomal RNA gene (LSU rDNA), partial DNA-directed RNA polymerase II subunit one gene ( rpb1 ) and subunit two gene ( rpb2 ), and partial translation elongation factor 1-alpha gene ( tef1 α) were amplified with primer pairs ITS 4 (5′-TCC TCC GCT TAT TGATAT GC-3′) and ITS 5 (5′-GGA AGT AAA AGT CGT AAC AAG G-3′; White et al, 1990 ), LR0R (5′-ACC CGC TGA ACT TAA GC-3′) and LR7 (5′-TAC TAC CAC CAA GAT CT-3′), RPB1-Af (5′-GAR TGY CCD GGD CAY TTY GG-3′) and RPB1-Cf (5′-CCN GCD ATN TCR TTR TCC ATR TA-3′; Matheny et al, 2002 ), fRPB2-5F (5′-GAY GAY MGW GAT CAY TTY GG-3′) and fRPB2-7cR (5′-CCC ATR GCT TGY TTR CCC AT-3′; Liu et al, 1999 ; Matheny, 2005 ), and EF1-1567R (5′-ACH GTR CCR ATA CCA CCS ATC TT-3′) and EF1-983F (5′-GCY CCY GGH CAY CGT CAY TTY AT-3′; Rehner and Buckley, 2005 ; Matheny et al, 2007 ), respectively. The polymerase chain reaction (PCR) procedures were as follows: for ITS sequences, an initial denaturation at 95°C for 3 min, followed by 34 cycles at 94°C for 40 s, 54°C for 45 s, 72°C for 1 min, and a final extension of 72°C for 10 min ( Zhou et al, 2021a , b ); for LSU rDNA region, an initial denaturation at 94°C for 1 min, followed by 34 cycles at 94°C for 30 s, 50°C for 1 min, 72°C for 1.5 min, and a final extension of 72°C for 10 min ( Shen et al, 2016 ); for rpb1 , rpb2 , and tef1 α regions, an initial denaturation at 94°C for 2 min, followed by 10 cycles at 94°C for 40 s, 60°C for 40 s, and 72°C for 2 min, then followed by 37 cycles at 94°C for 45 s, 55°C for 1.5 min, 72°C for 2 min, and a final extension at 72°C for 10 min ( Chen et al, 2015 ; Wang X. W. et al, 2021 ). Sequencing for PCR products was conducted by BGI Tech Solutions Beijing Liuhe Co., Ltd., Beijing, China.…”
Section: Methodsmentioning
confidence: 99%